The Urgency of Indonesian Anti-Terrorism Law: How We Combat Terrorist for the Future? - Tastama, Ridho Dwiky (Law Research Review Quarterly, 2021)
On 18 October 2002, Anti-Terrorism Law also known as ATL was signed into law by Megawati Soekarnoputri This kind of law has caused a significant legal controversy in because this law signed only six days after the unfamous Bali Bombings took place on 12 October 2002. Actually, The Law itself had first been drafted in 2002 more precisely on April on response to the then most recent terrorist incident which opened the eyes of global citizen from the danger of terrorism, the 9/11 incident in New York 2001. From 2002, The Anti-Terrorism LAW has been used to punish and investigate those who involved in the many incident such as the bombing of the Marriot Hotel in 2003, the Australian Embassy incident in September 2004, and the round two of Bali bombing which take place in October 2005. Since 2005 the proposed revision of the Anti-Terrorism Law getting stronger and more stronger. The proposed revision mainly talk about the addition of term of arrest and detention.